The outcomes of work-integrated learning programmes: The role of self-confidence as mediator between interpersonal and self-management skills and motivation to learn - Ibrahim H.I.; Jaafar A.H. (Universiti Putra Malaysia, 2023)
Work-integrated learning (WIL) is regarded as an important vehicle to assist undergraduates' employability skills, knowledge, and attributes that can add value to their learning, career aspiration and employability. There is limited research on the outcomes of WIL programmes in terms of undergraduates' personal and psychological attributes, and motivation to learn. This study examines the relationship between self-management and interpersonal skills, self-confidence, and motivation to learn through a survey of 383 business degree undergraduates from five Malaysian public universities who have participated in various WIL programmes. Results show that the students' motivation to learn is influenced by their self-management and interpersonal skills and mediated by their self-confidence. This finding provides a valuable insight into the outcomes of WIL programmes such as personal and psychological attributes and motivation to learn in order to ensure the effectiveness of WIL programmes in producing employable and lifelong learning graduates. 2017 Universiti Putra Malaysia Press.